Community Service Program for the Munsalo Farmers Group, Kuansing Regency, Riau - Wedayanti, Made Devi; Mardianti, Desy; Yogia, Moris Adidi; Pulungan, Boby Indra; Nurhafiza, (Jurnal Pengabdian Masyarakat, 2024)
Purpose: The primary aim of this community service initiative is to address the lack of bookkeeping among farmers in the Munsalo Kopah Farmers Group and the inadequate packaging of their rice, currently sold in used sacks and black plastic bags. This research is significant as it seeks to enhance the farmers' administrative practices and product presentation, improving income management and marketability. Method: The initiative employs training sessions on administrative management and effective packaging. Workshops focus on bookkeeping techniques and creating appealing packaging. Additionally, administrative tools and branded sacks for the Munsalo Kopah Farmers Group's rice are provided. Practical Applications: The initiative's outcomes have practical implications, enabling farmers to manage their finances better and enhance their product presentation. Improved packaging increases market competitiveness, providing significant advantages for better sales and customer engagement. Conclusion: This community service initiative effectively resolves key issues in administration and product packaging for the Munsalo Kopah Farmers Group. The positive feedback received highlights its importance, contributing to a better understanding of the need for enhanced practices in agricultural communities and promoting the farmers' economic well-being.